Diversify or die - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2006)
EU trade preferences have long been crucial to ACP countries operating on the margins of the world economy. But recent changes in trading rules now threaten the banana and sugar industries, and the small-scale producers who rely on them. Can they find new